Probability : - Durrett, Richard (Thomson Brooks/Cole, 2005)
Modern and measure-theory based, this text is intended primarily for the first-year graduate course in probability theory. The book focuses attention on examples while developing theory. There is an emphasis on results that can be used to solve problems in the hopes that those who apply probability to work will find this a useful reference.